Konsep Khauf dan Rajā Menurut Abū Ismā’īl ‘Abdullāh Al-Ansārī Al-Harawī Dalam Meningkatkan Kualitas Spiritual - Fahmiullah, Jiddan (Jurusan Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Adab UIN Sultan Maulana Hasanuddin Banten, 2023)
This study aims to examine the thoughts brought by the salaf scholars, Abū Ismā'īl 'Abdullāh Al-Ansārī Al-Harawī. This is based on his unique and controversial thoughts in his time so that he was often criticized by some people until he was put in prison, one of his controversial thoughts is about fana', from this fanā' theory Abū Ismā'īl 'Abdullāh's thoughts are seen that some people who hate will consider that Abū Ismā'īl 'Abdullāh is an extreme person who can mislead people. not only about fanā' which is labeled as a theory that can mislead people, It is not only fanā' that is labeled as a misleading theory, but also the theory of hope, which assumes that rajā' is the lowest maqām. This theory has been criticized by Ibn Qayyim al-Jauziyyah, but Ibn Qayyim al-Jauziyyah loved Abū Ismā'īl 'Abdullāh very much. The author uses qualitative literature research methods and interpretative analysis, the author seeks to collect data then analyze, filter and quote various data sources which are then interpreted in order to obtain a valid conclusion. The results of the study show that fear is a release from peace and security by knowing a news, what is meant by news (preaching) is knowing the news that comes from Allah, both in the form of promises and threats, while rajā' is a weak position for those who walk to Allah, because rajā' has two sides, namely, the side that describes resistance and the side that describes protest.